Sex and relationships education for LGBT+ young people: Lessons from UK youth work. (October 2020) - Formby, Eleanor; Donovan, Catherine
Lesbian, gay, bisexual and trans (LGBT) inclusive sex and relationships education (SRE) is of growing interest. However, there is a lack of clarity about what LGBT inclusive SRE should/does look like in practice. This article addresses that uncertainty by examining original research findings on innovative youth work based SRE provided within an arts-based project run by a third sector organisation in the North East of England. The research is set within the context of three broad rationales for LGBT inclusive SRE: to support the mental health of LGBT+ young people; to tackle sexual health issues, and to address concerns about sexual encounters and intimate relationships. The article sets out research findings within four main themes concerning: young people's experiences of formal SRE; young people's attempts to acquire SRE informally; young people's experiences of youth work based SRE; practitioners' experiences of delivering youth work based SRE. It then draws on this data to make the case for dedicated youth work for LGBT+ young people, outlining its potential alongside school-based SRE.